Estudo a campo do efeito do tratamento de sementes com inseticida e fungicida na capacidade de promoção do crescimento do trigo induzido por Azospirillum brasilense Ab- V5 e Ab- V6 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Azospirillum brasilense is the most studied plant growth promoting bacterium (PGPB) for use in grass crops. Field experiments with selected strains resulted in the first strains authorized for the production of inoculants in Brazil. Among these strains, Ab-V5 and AbV6 are the most recommended for the cultivation of wheat. However, in many cases the same growth promotion results obtained under controlled conditions have not been observed in the field. Insecticides and fungicides applied to seeds can reduce the number of viable bacterial cells and cause poor bacteria colonization. The objective of this work was to evaluate the effect of the inoculation of Azospirillum brasilense strains AbV5 and AbV6 in seeds previously treated with insecticide (Imidacloprid + Tiodicarb) and fungicide (Triadimenol), in the development and productivity of the wheat crop, cultivate TBIO Sossego. The experimental design was randomized blocks, with three replications, in a factorial scheme (3x3), represented by combinations of seed treatment and inoculation of Azospirillum brasilense. There was no difference for seedling emergence and number of tillers between the treatments tested. The inoculation of A. brasilense shortly before sowing combined with seed treatment and cell protector provided better levels of leaf chlorophyll measured at flowering. The inoculation of the seeds with A. brasilense 24 h before sowing was equivalent to not carrying out the inoculation for the parameters: leaf chlorophyll index, grains per ear, weight of a thousand grains. The highest yields of wheat grains were obtained when the seed treatment, cell protector and inoculation technologies of A. brasilense (shortly before sowing) were combined. The increase in wheat productivity with the combined use of these technologies was up to 16% or 671.82 kg ha-1 in relation to the control treatment (without inoculation and without seed treatment). The maximum yield reached was 4,771 kg ha-1, exceeding the grain yield expectations based on the fertilizer recommendation adopted. There were no effects of treatments for N content in the grains and N accumulation (kg ha-1).
Keywords: BPCV; Triticum aestivum; Imidacloprid + Tiodicarb; Triadimenol; PGPB; Triticum aestivum; Imidacloprid + Tiodicarb; Triadimenol; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA